Continuous Improvement Strategies for Enhancing the Quality of Learning at SDN 004 Bontang Barat - Tunggal, Anggunan; Hidayat, Syafril; Baco, Asmar; Azainil, Azainil (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to explore continuous improvement strategies in enhancing the quality of learning at SDN 004 Bontang Barat. Using a qualitative approach supported by descriptive data, the research identifies key factors influencing learning quality, implementation of continuous improvement strategies, implementation challenges, and stakeholder involvement. The findings show that strategies such as improving teacher competence, strengthening school management, integrating technology, upgrading infrastructure, and fostering collaboration with parents and the community have a positive impact on learning effectiveness. However, challenges such as limited resources, resistance to change, and lack of policy support must be addressed systematically. This study recommends fostering a reflective and evaluative school culture, visionary leadership, and sustained support from all stakeholders to achieve optimal learning quality. The continuous improvement strategies implemented at SDN 004 Bontang Barat demonstrate the importance of a holistic approach to enhancing learning quality. By addressing multiple aspects such as teacher competence, school management, technology integration, and community engagement, the school has created a more conducive environment for effective learning.